The flying hill profile as a limiting factor in the development of a world record in ski flying - Jost, B.; Vodicar, J. (Sciene and nordic skiing III, 2016)
Ski jumping is a popular sport that attracts crowds of spectators and viewers. The development of record-breaking flights has been closely related to the increase in flying hill sizes. The world`s longest jump of 251.5 m was made by Norwegian Anders Fannemel on the Vikersundbakken hill on 15th February 2015. Fannemel's in-run velocity in the record-breaking jump was a low 99.0 km/h. The wind conditions were excellent (wind point reduction -13.5 points). However, the landing was rather difficult and Fannemel sustained injury to his thigh muscles. On the same day, Russian jumper Dimitri Vassiliev flew 254 m but touched the snow on landing. His in-run velocity (101.0 km/h) was two kilometers higher than Fannemel`s. Due to its low altitude, the Vikersund flying hill provides ski jumpers very good aerodynamic conditions. The highest number of world records to date have been set on the flying hill in Planica, which was constructed by the GoriSek brothers. In 1936 Sepp Bradl became the first person to break the 100-meter mark. In 1994 the 200-metre mark was first beaten, again in Planica. The last world record set on the Planica hill dates back to 2005 when Norwegian Bjom Einar Romoren landed at 239 meters. After him, Janne Ahonen from Finland flew 240 m, but fell on landing. The curve of his flight was too high, and so was the pressure at the landing. A simulation of Ahonen`s flight showed that on the enlarged Planica hill of HS300m, the flight would end at 280 m (Figure 1). On the same hill, the 233 m jump which Simon Amman from Switzerland made in 2009 would land at the 303 m mark (Joßt, Coh & VodiCar, 2013).